Self-medication practices among female students of higher educational institutions in Selangor, Malaysia: A quantitative insight - Jamshed, Shazia Qasim; Wong, Peise; Yi, Hengchin; Yun, Gansiaw; Khan, Muhammadumair; Ahmad, Akram (Medknow Publications and Media Pvt. Ltd, 2016)
Background: World Health Organization has defined self-medication as the selection and use of medications (including herbal and traditional product) by individuals to treat self-recognized illnesses or symptoms. The prevalence of self-medication is reported to be higher among female students. Objective: To investigate the awareness and self-medication practices among female students of higher education institutions in Malaysia. Method: A descriptive, cross-sectional study was conducted in four higher education institutes of Selangor, Malaysia. Convenience sampling approach was used to collect data from a sample 475 students. A 'pretested' questionnaire was used as a study instrument. Results: A total of 461 questionnaires were returned (response rate 97.05%). The prevalence of self-medication among female students in higher educational institutions was 57.2% (n = 262). The most common source of self-prescribed medicine was a pharmacy or clinics (n = 206; 45%). It was found that antipyretics were the most common medications used without doctor's consultation (n = 212; 89.1%). Analgesics and antipyretics (n = 79; 62.7%) were highly recommended by students to their family and friends. The common reason for self-medication was prior successful experience (n = 102, 81.0%). The majority of respondents (n = 280; 61.1%) reported that they believed over-the-counter medications were as effective as medications prescribed by a doctor. Conclusion: The prevalence of self-medication practice among female students in the sample of the four higher education institutions was moderate. More studies are required to generalize these findings across Malaysia.